Three Positive Periodic Solutions of Nonlinear Functional Difference Equations - Liu, Yuji; Liu, Xingyuan (Sarajevo Journal of Mathematics, 2024)
Sufficient conditions for the existence of at least three positive $T$-periodic solutions of the nonlinear functional difference equations are established. An example is presented to illustrate the main results. 2000 Mathematics Subject Classification. 34B10, 34B15